Mindfulness Therapy to Lower the Tendency to Fear of Missing Out (FoMo) - Lisda Sofia; Rina Rifayanti; Putri Rizki Amalia; Louise Monica Kurnia Gultom (Universitas Aisyah Pringsewu, 2023)
This research was conducted to decide the effectiveness of mindfulness therapy in reducing the tendency of fear of missing out (FoMO) for Z generation who are active in using social media Instagram. This study used a research design in the form of a two-group pre-test post-test design. The subjects in this study were 16 generation Z Instagram users who were divided into two groups, namely 8 Z generation of Instagram users who were included in the experimental group and 8 generation Z Instagram users who were included in the control group. Measurement of the fear of missing out (FoMO) tendency experienced by research subjects was measured using the fear of missing out (FoMO) scale adapted. The data analysis used in this study was the Wilcoxon test and the Mann-Whitney U Test using SPSS 26 for Windows software. The results of the analysis obtained using the Wilcoxon test by comparing the score of fear of missing out (FoMO) in the experimental group between before and after giving mindfulness therapy treatment showed a value of Z = -2.384 and a value of p = 0.017 (p less than 0.05), which means that there is a difference fear of missing out (FoMO) scores before and after being given mindfulness therapy, so there was a significant decrease in fear of missing out (FoMO) after being given mindfulness therapy. Based on the results of the analysis using the Mann-Whitney U Test, the value of Z = -1.481 and the p value = 0.139 (p more than 0.05), which means that there is no difference in the level of fear of missing out (FoMO) between the experimental group given mindfulness therapy treatment and the control group who did not. given mindfulness therapy treatment.Abstrak: Penelitian ini dilakukan untuk mengetahui efektivitas mindfulness therapy dalam mengurangi kecenderungan fear of missing out (FoMO) bagi generasi Z yang aktif menggunakan media sosial Instagram. Penelitian ini menggunakan desain penelitian berupa desain pre-test post-test dua kelompok. Subjek dalam penelitian ini adalah 16 pengguna Instagram generasi Z yang dibagi menjadi dua kelompok, yaitu 8 pengguna Instagram generasi Z yang masuk dalam kelompok eksperimen dan 8 pengguna Instagram generasi Z yang masuk dalam kelompok kontrol. Pengukuran kecenderungan fear of missing out (FoMO) yang dialami subjek penelitian diukur menggunakan skala fear of missing out (FoMO) yang disesuaikan. Analisis data yang digunakan dalam penelitian ini adalah uji Wilcoxon dan Uji U Mann-Whitney menggunakan SPSS 26 untuk software Windows. Hasil analisis yang diperoleh dengan menggunakan uji Wilcoxon dengan membandingkan skor fear of missing out (FoMO) pada kelompok eksperimen antara sebelum dan sesudah pemberian perlakuan mindfulness therapy menunjukkan nilai Z=-2,384 dan nilai p=0,017 (p kurang dari 0,05), yang berarti terdapat perbedaan skor fear of missing out (FoMO) sebelum dan sesudah diberikan mindfulness therapy, jadi ada penurunan yang signifikan dalam fear of missing out (FoMO) setelah diberi terapi mindfulness. Berdasarkan hasil analisis menggunakan Mann-Whitney U Test, nilai Z = -1,481 dan nilai p = 0,139 (p lebih dari 0,05), yang berarti tidak ada perbedaan tingkat fear of missing out (FoMO) antara kelompok eksperimen yang diberikan perlakuan mindfulness therapy dengan kelompok kontrol yang tidak. diberikan perlakuan mindfulness therapy.